Comparing PVP and polymeric micellar formulations of a PEGylated photosensitizing phthalocyanine by NMR and optical techniques - (:unkn) unknown (My University, 2023)
Phthalocyanines are ideal candidates as photosensitizers for photodynamic therapy (PDT) of cancer due to their favorable chemical and photophysical properties. However, their tendency to form aggregates in water reduces PDT efficacy and poses challenges in obtaining efficient forms of phthalocyanines for therapeutic applications. In the current work, polyvinylpyrrolidone (PVP) and micellar formulations were compared for encapsulating and monomerizing a water-soluble zinc phthalocyanine bearing four non-peripheral triethylene glycol chains (Pc1). 1H NMR spectroscopy combined with UV-vis absorption and fluorescence spectroscopy revealed that Pc1 exists as a mixture of regioisomers in monomeric form in dimethyl sulfoxide but forms dimers in an aqueous buffer. PVP, polyethylene glycol castor oil (Kolliphor RH40), and three different triblock copolymers with varying proportions of polyethylene and polypropylene glycol units (termed P188, P84, and F127) were tested as micellar carriers for Pc1. 1H NMR chemical shift analysis, diffusion-ordered spectroscopy, and 2D nuclear Overhauser enhancement spectroscopy was applied to monitor the encapsulation and localization of Pc1 at the polymer interface. Kolliphor RH40 and F127 micelles exhibited the highest affinity for encapsulating Pc1 in the micellar core and resulted in intense Pc1 fluorescence emission as well as efficient singlet oxygen formation along with PVP. Among the triblock copolymers, efficiency in binding and dimer dissolution decreased in the order F127 > P84 > P188. PVP was a strong binder for Pc1. However, Pc1 molecules are rather surface-attached and exist as monomer and dimer mixtures. The results demonstrate that NMR combined with optical spectroscopy offer powerful tools to assess parameters like drug binding, localization sites, and dynamic properties that play key roles in achieving high host-guest compatibility. With the corresponding adjustments, polymeric micelles can offer simple and easily accessible drug delivery systems optimizing phthalocyanines\" properties as efficient photosensitizers.
Keywords: Tıp; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; TROPİKAL TIP; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; TROPICAL MEDICINE; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Tıp; Farmasötik bilim; İlaç Keşfi; Molecular Medicine; Pharmaceutical Science; Drug Discovery; drug delivery; fluorescence spectroscopy; Kolliphor RH40; NMR spectroscopy; photosensitizer; phthalocyanine; polymer micelles; PVP; triblock copolymers; phthalocyanine; photosensitizer; drug delivery; polymer micelles; PVP; triblock copolymers; Kolliphor RH40; NMR spectroscopy; fluorescence spectroscopy